Distinctive features of the development of the advertising market of the Republic of Kazakhstan - Sadykova Zh.M. , Садыкова Ж.М.; Sagimbekova А.М. , Сагимбекова А.М. (Рroblems of engineering and professional education, 2023)
The article deals with the development of the advertising market, the formation of advertising as an economic activity and a form of social and cultural order in the Republic of Kazakhstan. Analyzed the domestic advertising market and the changes occurring in the advertising market and the factors on which they depend.